2021
DOI: 10.1021/acsmaterialslett.1c00566
|View full text |Cite
|
Sign up to set email alerts
|

Turning the Byproduct Zn4(OH)6SO4·xH2O into a Uniform Solid Electrolyte Interphase to Stabilize Aqueous Zn Anode

Abstract: Aqueous Zn anodes suffer from continuous side reactions and severe dendrite growth upon Zn plating and stripping, mainly due to the lack of an efficient protective layer. Herein, we report a facile approach to turn the byproduct Zn 4 (OH) 6 SO 4 •xH 2 O (ZHS) into a uniform solid electrolyte interphase (SEI) by simply introducing a small amount Zn(OH) 2 into the ZnSO 4 electrolyte. It is revealed that the uniform ZHS-based SEI possesses low electronic conductivity, high Zn 2+ ion conductivity, and high zincoph… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
45
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(46 citation statements)
references
References 54 publications
1
45
0
Order By: Relevance
“…[10] Chen et al demonstrated that SeO 2 additives (2 mm) is capable of forming ZnSe protective layer on the Zn surface, but the cycle stability under harsh test condition is still undesired. [9a] Other SEI forming agents have also been reported, including Zn(H 2 PO 4 ) 2 , [11] SnCl 2 , [12] DMSO, [9b] triethyl phosphate, [13] Zn(OH) 2 , [14] KPF 6 , [15] and In(OTf) 3. [16,5a,17] Despite great progress, building robust SEI still necessitates a substantial amount of electrolyte additives, increasing the electrolyte cost and the irreversible consumption of Zn cations and/or electrons.…”
Section: Doi: 101002/smll202203674mentioning
confidence: 99%
“…[10] Chen et al demonstrated that SeO 2 additives (2 mm) is capable of forming ZnSe protective layer on the Zn surface, but the cycle stability under harsh test condition is still undesired. [9a] Other SEI forming agents have also been reported, including Zn(H 2 PO 4 ) 2 , [11] SnCl 2 , [12] DMSO, [9b] triethyl phosphate, [13] Zn(OH) 2 , [14] KPF 6 , [15] and In(OTf) 3. [16,5a,17] Despite great progress, building robust SEI still necessitates a substantial amount of electrolyte additives, increasing the electrolyte cost and the irreversible consumption of Zn cations and/or electrons.…”
Section: Doi: 101002/smll202203674mentioning
confidence: 99%
“…S10 and S11 †). 61,62 Fig. S12 † presents the cyclic voltammetry (CV) curves of ZnkPANI full cells in the two electrolytes at 2 mV s À1 , both of which demonstrate the typical redox peaks of PANI, 61 suggesting that the addition of the DPA additive would not change the redox process of PANI.…”
Section: Resultsmentioning
confidence: 99%
“…On the other hand, the formation of ZnO byproducts with O 2 in the system may passivate the deposited zinc. [41,50] The Zn dendrites and ZnO eventually cause severe irreversibility and low efficiency of Zn anode. By adding low amounts of Li and Mn into Zn, however, we can inhibit the growth of Zn dendrites with a much more uniform deposition of Zn during long-time cycles.…”
Section: Electrochemical Properties Of the Znlimn Alloysmentioning
confidence: 99%